Potensi Air Leri sebagai Pupuk Organik untuk Pakcoy (Brassica rapa L.) dengan Hidroponik DFT Model Meja - Sapto Wibowo (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
Leri water is rice washing wastewater which has been only thrown away by the community, is easily produced or obtained every day, and can be used as organic fertilizer in plant cultivation. This study aims to determine the potential of leri water as organic fertilizer for pakcoy plants with table model DFT hydroponics. This research method was carried out using three nutrient solution treatments, namely leri water (N1), leri water + AB mix with a ratio of 1:1 (N2), and AB mix (N3). The results of the measurement of the number of leaves (strands), plant height (cm), and plant weight (g) in the three nutrient solution treatments were compared to determine whether there was a difference using one-way ANOVA with a level of 5%. If the results are significantly different, then proceed with the Tukey's HSD test at the 5% level. The results showed that leri water has the potential as a liquid organic fertilizer when added to AB mix fertilizer, with a ratio of 1:1 (N2) can increase the weight of pakcoy plants by four times the yield of N1.